Clinical Characteristics of Pregnancy-Associated Central Serous Chorioretinopathy in the Chinese Population. (16th December 2021) - Yu, Jia; Li, Lei; Jiang, Chunhui; Chang, Qing; Xu, Gezhi
Abstract : Purpose . To investigate the clinical characteristics of pregnancy-associated central serous chorioretinopathy (CSC) in the Chinese population. Methods . The medical records of patients diagnosed with pregnancy-associated CSC from February 2012 to October 2019 were retrospectively reviewed. Best-corrected visual acuity (BCVA), symptom duration, pregnancy-related medical information, and optical coherence tomography (OCT) images were collected. Results . Nine patients (11 eyes) were included. Five women were in their first pregnancy and four were in their second pregnancy, two of whom experienced CSC in their first pregnancy as well. The mean age was 35.00 ± 3.97 years. The mean symptom duration at the initial visit was 19.73 ± 13.65 days. The mean gestational age at the time of development of CSC was 27.11 ± 2.09 weeks. The mean BCVA (logarithm of the minimum angle of resolution (logMAR)) at the initial visit was 0.36 ± 0.18 (Snellen 20/45, range 20/100–20/25). All eyes showed subretinal hyperreflective fibrin on OCT images at the initial visit. Four patients (4 eyes) were lost to follow-up before fluid resolution. The mean BCVA at the final visit was logMAR 0.10 ± 0.15 (Snellen 20/25, range 20/50–20/20)). One eye in the oldest patient had persistent subretinal fluid at 26 months postpartum. The subretinal fluid resolved completely after half-dose photodynamic therapy (PDT); however, the ellipsoid zone at the fovea remained discontinuous at 30 months after half-dose PDT. The remaining six eyes all showed spontaneous resolution of subretinal fluid around delivery and regained intact ellipsoid zone. Conclusions . Pregnancy-associated CSC in Chinese developed mostly in the third trimester and usually recovered spontaneously around delivery with good final visual acuity. However, patients might require long-term follow-up until complete resolution of subretinal fluid and to detect recurrences. Half-dose PDT can be administered early if there is little reduction in the amount of subretinal fluid after delivery.